KUALITAS PELAYANAN PUBLIK BIDANG KESEHATAN PASCA BENCANA GEMPA BUMI DITINJAU DARI DIMENSI KEYAKINAN DAN DIMENSI EMPATI DI BENGKULU UTARA - Salamun - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to describe the quality of public services in health after the earthquake in North Bengkulu with study site in Services Agency General Hospital North Bengkulu Region. The focus of this research study aimed at two main dimensions of public services quality, namely confidence and empathy. The method used was qualitative method with the goal of implementing the apparatus and the service selected by using purposive and accidental sampling. Methods of data collection used in-depth interviews, observation and documentation techniques. Data analysis used descriptive qualitative techniques with interactive model. The results showed: (1) from dimension of faith, the Services officers Agency of North Bengkulu General Hospital have sufficient competence and attitude in giving service, (2) from the dimensions of empathy, the officers have the willingness and efforts to empathize with the conditions of service users. In general, the quality of public services in the Services officers Agency of North Bengkulu General Hospital has met both criteria. Because the two major dimensions that are the focus of this research can be done properly in accordance with the desired service standards by the service users (costumers).